Compact femtosecond fiber laser tunable from 800 to 850 nm with pulse energy exceeding 5 nJ - Dmitrii Stoliarov; Aleksandr Koviarov; Diana Galiakhmetova; Edik Rafailov (Scientific Reports)
Abstract This paper introduces a compact, tunable femtosecond laser based on an Erbium-doped fiber, utilizing the Self-Soliton Frequency Shifted technique and PPLN crystal as a Second Harmonic Generation module. Achieving an unparalleled frequency conversion efficiency up to 55% for the 800 - 850 nm wavelength range, this compact laser emits sub-100 fs pulses. The laser operates simultaneously within the first and third biological windows, delivering pulse energies of 10.4 nJ and 5.1 nJ, respectively. This performance, previously unattained in similar systems, is achieved while maintaining Second Harmonic Generation power stability below 2% RMS. The presented compact laser, developed for bladder cancer detection through multiphoton microscopy, will significantly improve the system’s compactness, precision, and cancer detection efficiency.